1993
DOI: 10.1007/bf00225019
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of heat-stable resistance to Meloidogyne incognita in Lycopersicon peruvianum and its relationship to the Mi gene

Abstract: The inheritance of heat-stable resistance to the root-knot nematode, Meloidogyne incognita (Kofoid and White) Chitwood, was studied in crosses between different accessions and clones of Lycopersicon peruvianum L. F1, F2 and BC1 generations were evaluated for their index of resistance based on numbers of eggs and infective second-stage juveniles (J2) per gram of root, and the segregation ratios were determined in experiments carried out at constant soil temperatures of 25 °C and 30 °C. L. peruvianum P.I. 270435… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 11 publications
1
24
0
3
Order By: Relevance
“…nematodes virulent on Me3-resistant peppers were not able to reproduce on Mel-resistant peppers). Concordant observations had already been made for tomato, in which resistance was found against selected Mi-virulent M. incognita isolates (Roberts et al, 1990), and later identified as partly due to the gene Mi-2 (Cap et al, 1993). Very recently, a new resistance locus was identified in Lycopersicon peruvianum, and this gene, designated Mi-3, was shown to confer resistance against a M. incognita strain that can infect plants carrying Mi (Yaghoobi et al, 1995).…”
Section: Discussionmentioning
confidence: 76%
“…nematodes virulent on Me3-resistant peppers were not able to reproduce on Mel-resistant peppers). Concordant observations had already been made for tomato, in which resistance was found against selected Mi-virulent M. incognita isolates (Roberts et al, 1990), and later identified as partly due to the gene Mi-2 (Cap et al, 1993). Very recently, a new resistance locus was identified in Lycopersicon peruvianum, and this gene, designated Mi-3, was shown to confer resistance against a M. incognita strain that can infect plants carrying Mi (Yaghoobi et al, 1995).…”
Section: Discussionmentioning
confidence: 76%
“…Upon digestion with either SacI or BamHI, the band from the resistant parent was cleaved into two fragments, while that of the susceptible parent was not cleaved. Because additional root-knot nematode resistance genes that are unlinked to Mi have been identi®ed in L. peruvianum (Cap et al 1993;Yaghoobi et al 1995;Veremis and Roberts 1996a), F2 progeny were assayed to con®rm segregation of nematode resistance with Milinked markers from the resistant accession.…”
Section: Molecular Markers In the MI Regionmentioning
confidence: 99%
“…L. peruvianum is a heterogeneous species, with accessions and individuals within accessions diering in marker alleles as well as in nematode resistance (Miller and Tanksley 1990;Yaghoobi et al 1995). Several different root-knot nematode resistance genes have recently been identi®ed within accessions of this species (Cap et al 1993;Yaghoobi et al 1995;Veremis and Roberts 1996b, c). We developed a population of plants segregating for resistance due to Mi and identi®ed recombinants with crossovers near Mi by using PCR-based anking markers.…”
Section: Introductionmentioning
confidence: 98%
“…For example, new sources of root-knot nematode resistance have been identified in accessions of S. peruvianum (Ammati et al, 1985(Ammati et al, , 1986. Inheritance studies of some of these new resistance traits have revealed the presence of additional genes that segregate independently of Mi-1 (Cap et al, 1993;Veremis and Roberts, 1996b). These genes were distinguished according to resistance phenotype at high temperature or resistance to Mi-1-virulent nematode isolates Roberts, 1996a, 1996b).…”
mentioning
confidence: 99%